Estimation of tidally influenced estuarine river discharge from space using along‐track InSAR technology: A model‐based feasibility study. Issue 7 (30th July 2013) - Grünler, S.; Romeiser, R.; Stammer, D.
Abstract : [1] We discuss the potential of the along‐track interferometric synthetic aperture radar (along‐track InSAR, ATI) technique for monitoring tidally influenced estuarine river discharge from space. To observe river discharge using ATI, surface velocity measurements need to be converted to depth‐integrated velocity to apply empirical discharge models and, possibly aliased, tidal signals need to be removed. Problems may also arise from the fact that ATI velocity observations generally are not in the along‐flow direction, and from uncertainties in applied empirical discharge models. To quantify the degree to which river discharge can be inferred from ATI data, output from a high‐resolution numerical model of the Elbe estuary serves here as the basis for simulated observations of a TerraSAR‐X‐like satellite mission as well as simulated ground truth against which retrieved transports are tested. Results show that with only the additional information of the river widths, instantaneous discharge estimates can be obtained from ATI‐derived velocities. To retrieve mean discharges from a number of instantaneous measurements at different tidal phases, we fit time series of the tidal components M 2 and K 1 to the data by amplitude and phase adjustment and subtract them. We demonstrate the successful application of such a mean‐value estimator for calculating net discharges. A simulated TerraSAR‐X sampling scenario provides discharge estimates for the Elbe estuary with accuracies in the range of 20–30%, comparable in quality to commonly used ground‐based noncontact discharge measurements. The proposed satellite‐based monitoring approach, therefore, provides a promising new method for river discharge estimates in estuaries, especially in regions where onsite measurements are not possible or data are not accessible. Key Points: Estimation of river discharge using along‐track InSAR current measurements Simulations of observations of a TerraSAR‐X‐like satellite mission Estimation of total global annual mean river freshwater input into the ocean